Multiple Criteria Evaluation of Influence of Components of Entrepreneurship Education Programmes on Formation of Competencies - Ruškytė, Lect. Dr. Džiuljeta; Bajraktari, Halim; Lata, Flori (European Journal of Economics and Business Studies, 2017)
The article substantiates the concept of entrepreneurship education from the holistic perspective, which is interpreted in the context of education in its broad meaning and is related to knowledge, abilities of economics and business, value orientations, personal traits and their comprehensive development. The significance of content areas of the General Education Curriculum to development of entrepreneurship skills in schools of general education in Lithuania was analysed. Multiple criteria evaluation, based on expert evaluations, was applied for evaluation of significance of areas of the programme content mathematically processing and systemising the data. The significance of areas of programme content evaluated by experts was established using methods of indirect evaluation (ranking) and direct evaluation (percentage expression). The research showed that the data of expert evaluations, conducted using the methods of indirect and direct evaluation, coincide and, therefore, the data can be regarded as reliable. The conducted mathematical calculations show that multiple criteria methods can be successfully applied evaluating any other programme of similar kind.